Peningkatan Literasi Keuangan Siswa Madrasah Ibtidaiyah Muhammadiyah (MIM) Program Khusus 1 Sindon melalui Kelas Literasi Keuangan berbasis Alam - Sari, Dhany Efita; Suranto, Suranto; Santhyami, Santhyami; Sayekti, Ika Candra; Wahyudi, Tri Nur; Fadhilah, Risma; Putri, Listi Septiana Avita; Setianingrum, Septi; Azizah, Faritsa Syifa; Rahmania, Intan Putri (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2024)
ABSTRACT The financial literacy mentorship program, which is focused on outdoor classroom activities at Madrasah Ibtidaiyah Muhammadiyah Program Khusus (MIM PK) 1 Sindon Boyolali, was initiated in response to elementary school pupils' lack of understanding of financial management. Many youngsters prioritize wants above needs and fail to understand the necessity of financial management at a young age. The program aims to improve kids' financial literacy through hands-on experiences and outdoor learning, while simultaneously raising environmental consciousness. The program employs a variety of tactics, including modeling buying and selling using toy money and veggies, sowing vegetable seeds in recycled plastic bottles, and organizing a Market Day where kids sell their produce. Students are taught the fundamentals of transactions, financial planning, and simple entrepreneurship. University students enrolled in the Accounting Education and Elementary School Teacher Education programs also mentor and assess the learning process. The program's results demonstrate that students' financial literacy improved significantly, with an average rise of 1.5 points between the pre-test and the post-test. Aside from financial literacy, kids learn the value of environmental stewardship through horticultural activities. This program successfully improves students' understanding of financial literacy while establishing environmentally conscious ideals.Keywords: financial literacy, outdoor classroom, green school, muhammadiyah elementary schoolABSTRAK Program pendampingan literasi keuangan berbasis kelas alam di Madrasah Ibtidaiyah Muhammadiyah Program Khusus (MIM PK) 1 Sindon Boyolali dilatarbelakangi oleh rendahnya pemahaman siswa sekolah dasar mengenai pengelolaan keuangan. Banyak siswa cenderung lebih fokus pada keinginan dibandingkan kebutuhan, serta belum memahami pentingnya mengelola keuangan sejak dini. Tujuan kegiatan ini adalah meningkatkan literasi keuangan siswa melalui pengalaman langsung dan pendekatan berbasis kelas alam, serta menanamkan kesadaran ramah lingkungan. Kegiatan ini dilaksanakan dengan berbagai metode, seperti simulasi jual beli menggunakan uang dan sayuran mainan, penanaman bibit sayuran di galon plastik bekas, serta Market Day yang melibatkan penjualan hasil panen. Siswa diajarkan konsep dasar transaksi, perencanaan keuangan, dan kewirausahaan sederhana. Mahasiswa dari Prodi Pendidikan Akuntansi dan PGSD juga terlibat dalam pendampingan dan evaluasi proses pembelajaran. Hasil dari program ini menunjukkan adanya peningkatan signifikan literasi keuangan siswa, dengan rata-rata peningkatan skor dari pretest sebesar 1,5 poin pada posttest. Selain peningkatan literasi keuangan, siswa juga belajar tentang pentingnya menjaga lingkungan melalui kegiatan bercocok tanam. Program ini berhasil memperkuat pemahaman siswa tentang literasi keuangan sekaligus menanamkan nilai-nilai peduli lingkungan.Kata kunci: literasi keuangan, sekolah alam, sekolah hijau, madrasah ibtidaiyah muhammadiyah